Understanding Climate's Influence on Human Evolution - National Research Council (The National Academies Press, 2010)
The hominin fossil record documents a history of critical evolutionary events that have ultimately shaped and defined what it means to be human, including the origins of bipedalism; the emergence of our genus Homo; the first use of stone tools; increases in brain size; and the emergence of Homo sapiens, tools, and culture. The Earth's geological record suggests that some evolutionary events were coincident with substantial changes in African and Eurasian climate, raising the possibility that critical junctures in human evolution and behavioral development may have been affected by the environmental characteristics of the areas where hominins evolved. Understanding Climate's Change on Human Evolution explores the opportunities of using scientific research to improve our understanding of how climate may have helped shape our species. Improved climate records for specific regions will be required before it is possible to evaluate how critical resources for hominins, especially water and vegetation, would have been distributed on the landscape during key intervals of hominin history. Existing records contain substantial temporal gaps. The book's initiatives are presented in two major research themes: first, determining the impacts of climate change and climate variability on human evolution and dispersal; and second, integrating climate modeling, environmental records, and biotic responses. Understanding Climate's Change on Human Evolution suggests a new scientific program for international climate and human evolution studies that involve an exploration initiative to locate new fossil sites and to broaden the geographic and temporal sampling of the fossil and archeological record; a comprehensive and integrative scientific drilling program in lakes, lake bed outcrops, and ocean basins surrounding the regions where hominins evolved and a major investment in climate modeling experiments for key time intervals and regions that are critical to understanding human evolution.
Keywords: Biology and Life Sciences; Earth Sciences

In the Light of Evolution: Volume II: Biodiversity and Extinction - National Academy of Sciences (The National Academies Press, 2008)
The current extinction crisis is of human making, and any favorable resolution of that biodiversity crisis—among the most dire in the 4-billion-year history of Earth—will have to be initiated by mankind. Little time remains for the public, corporations, and governments to awaken to the magnitude of what is at stake. This book aims to assist that critical educational mission, synthesizing recent scientific information and ideas about threats to biodiversity in the past, present, and projected future. This is the second volume from the In the Light of Evolution series, based on a series of Arthur M. Sackler colloquia, and designed to promote the evolutionary sciences. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. Individually and collectively, the ILE series aims to interpret phenomena in various areas of biology through the lens of evolution, address some of the most intellectually engaging as well as pragmatically important societal issues of our times, and foster a greater appreciation of evolutionary biology as a consolidating foundation for the life sciences.
Keywords: Biology and Life Sciences

Evolution in Hawaii: A Supplement to 'Teaching About Evolution and the Nature of Science' - National Academy of Sciences (The National Academies Press, 2004)
As both individuals and societies, we are making decisions today that will have profound consequences for future generations. From preserving Earth's plants and animals to altering our use of fossil fuels, none of these decisions can be made wisely without a thorough understanding of life's history on our planet through biological evolution. Companion to the best selling title Teaching About Evolution and the Nature of Science, Evolution in Hawaii examines evolution and the nature of science by looking at a specific part of the world. Tracing the evolutionary pathways in Hawaii, we are able to draw powerful conclusions about evolution's occurrence, mechanisms, and courses. This practical book has been specifically designed to give teachers and their students an opportunity to gain a deeper understanding of evolution using exercises with real genetic data to explore and investigate speciation and the probable order in which speciation occurred based on the ages of the Hawaiian Islands. By focusing on one set of islands, this book illuminates the general principles of evolutionary biology and demonstrate how ongoing research will continue to expand our knowledge of the natural world.
Keywords: Biology and Life Sciences; Education

Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation - National Research Council (The National Academies Press, 2012)
Evolution is the central unifying theme of biology. Yet today, more than a century and a half after Charles Darwin proposed the idea of evolution through natural selection, the topic is often relegated to a handful of chapters in textbooks and a few class sessions in introductory biology courses, if covered at all. In recent years, a movement has been gaining momentum that is aimed at radically changing this situation. On October 25-26, 2011, the Board on Life Sciences of the National Research Council and the National Academy of Sciences held a national convocation in Washington, DC, to explore the many issues associated with teaching evolution across the curriculum. Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation summarizes the goals, presentations, and discussions of the convocation. The goals were to articulate issues, showcase resources that are currently available or under development, and begin to develop a strategic plan for engaging all of the sectors represented at the convocation in future work to make evolution a central focus of all courses in the life sciences, and especially into introductory biology courses at the college and high school levels, though participants also discussed learning in earlier grades and life-long learning. Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation covers the broader issues associated with learning about the nature, processes, and limits of science, since understanding evolutionary science requires a more general appreciation of how science works. This report explains the major themes that recurred throughout the convocation, including the structure and content of curricula, the processes of teaching and learning about evolution, the tensions that can arise in the classroom, and the target audiences for evolution education.
Keywords: Education; Biology and Life Sciences

Twenty-First Century Ecosystems: Managing the Living World Two Centuries After Darwin: Report of a Symposium - National Research Council (The National Academies Press, 2011)
The two hundredth anniversary of the birth of Charles Darwin, February 12, 2009, occurred at a critical time for the United States and the world. In honor of Darwin's birthday, the National Research Council appointed a committee under the auspices of the U.S. National Committee (USNC) for DIVERSITAS to plan a Symposium on Twenty-first Century Ecosystems. The purpose of the symposium was to capture some of the current excitement and recent progress in scientific understanding of ecosystems, from the microbial to the global level, while also highlighting how improved understanding can be applied to important policy issues that have broad biodiversity and ecosystem effects. The aim was to help inform new policy approaches that could satisfy human needs while also maintaining the integrity of the goods and services provided by biodiversity and ecosystems over both the short and the long terms. This report summarizes the views expressed by symposium participants; however, it does not provide a session-by-session summary of the presentations at the symposium. Instead, the symposium steering committee identified eight key themes that emerged from the lectures, which were addressed in different contexts by different speakers. The focus here is on general principles rather than specifics. These eight themes provide a sharp focus on a few concepts that enable scientists, environmental NGOs, and policy makers to engage more effectively around issues of central importance for biodiversity and ecosystem management.
Keywords: Biology and Life Sciences; Environment and Environmental Studies

In the Light of Evolution: Volume III: Two Centuries of Darwin - National Academy of Sciences (The National Academies Press, 2009)
Two Centuries of Darwin is the outgrowth of an Arthur M. Sackler Colloquium, sponsored by the National Academy of Sciences on January 16-17, 2009. In the chapters of this book, leading evolutionary biologists and science historians reflect on and commemorate the Darwinian Revolution. They canvass modern research approaches and current scientific thought on each of the three main categories of selection (natural, artificial, and sexual) that Darwin addressed during his career. Although Darwin's legacy is associated primarily with the illumination of natural selection in The Origin, he also contemplated and wrote extensively about what we now term artificial selection and sexual selection. In a concluding section of this book, several science historians comment on Darwin's seminal contributions. Two Centuries of Darwin is the third book of the In the Light of Evolution series. Each installment in the series explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. The ILE series aims to interpret phenomena in various areas of biology through the lens of evolution and address some of the most intellectually engaging, as well as pragmatically important societal issues of our times.
Keywords: Biology and Life Sciences; Explore Science

Science, Evolution, and Creationism - National Academy of Sciences; Institute of Medicine (The National Academies Press, 2008)
How did life evolve on Earth? The answer to this question can help us understand our past and prepare for our future. Although evolution provides credible and reliable answers, polls show that many people turn away from science, seeking other explanations with which they are more comfortable. In the book Science, Evolution, and Creationism, a group of experts assembled by the National Academy of Sciences and the Institute of Medicine explain the fundamental methods of science, document the overwhelming evidence in support of biological evolution, and evaluate the alternative perspectives offered by advocates of various kinds of creationism, including "intelligent design." The book explores the many fascinating inquiries being pursued that put the science of evolution to work in preventing and treating human disease, developing new agricultural products, and fostering industrial innovations. The book also presents the scientific and legal reasons for not teaching creationist ideas in public school science classes. Mindful of school board battles and recent court decisions, Science, Evolution, and Creationism shows that science and religion should be viewed as different ways of understanding the world rather than as frameworks that are in conflict with each other and that the evidence for evolution can be fully compatible with religious faith. For educators, students, teachers, community leaders, legislators, policy makers, and parents who seek to understand the basis of evolutionary science, this publication will be an essential resource.
Keywords: Biology and Life Sciences; Education

In the Light of Evolution: Volume V: Cooperation and Conflict - National Academy of Sciences (The National Academies Press, 2011)
Biodiversity—the genetic variety of life—is an exuberant product of the evolutionary past, a vast human-supportive resource (aesthetic, intellectual, and material) of the present, and a rich legacy to cherish and preserve for the future. Two urgent challenges, and opportunities, for 21st-century science are to gain deeper insights into the evolutionary processes that foster biotic diversity, and to translate that understanding into workable solutions for the regional and global crises that biodiversity currently faces. A grasp of evolutionary principles and processes is important in other societal arenas as well, such as education, medicine, sociology, and other applied fields including agriculture, pharmacology, and biotechnology. The ramifications of evolutionary thought also extend into learned realms traditionally reserved for philosophy and religion. The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia—in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences—and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium "Cooperation and Conflict," which was sponsored by the National Academy of Sciences on January 7-8, 2011, at the Academy's Arnold and Mabel Beckman Center in Irvine, California. It is the fifth in a series of colloquia under the general title "In the Light of Evolution." The current volume explores recent developments in the study of cooperation and conflict, ranging from the level of the gene to societies and symbioses. Humans can be vicious, but paradoxically we are also among nature's great cooperators. Even our great conflicts-wars-are extremely cooperative endeavors on each side. Some of this cooperation is best understood culturally, but we are also products of evolution, with bodies, brains, and behaviors molded by natural selection. How cooperation evolves has been one of the big questions in evolutionary biology, and how it pays or does not pay is a great intellectual puzzle. The puzzle of cooperation was the dominant theme of research in the early years of Darwin's research, whereas recent work has emphasized its importance and ubiquity. Far from being a rare trait shown by social insects and a few others, cooperation is both widespread taxonomically and essential to life. The depth of research on cooperation and conflict has increased greatly, most notably in the direction of small organisms. Although most of In the Light of Evolution V: Cooperation and Conflict is about the new topics that are being treated as part of social evolution, such as genes, microbes, and medicine, the old fundamental subjects still matter and remain the object of vigorous research. The first four chapters revisit some of these standard arenas, including social insects, cooperatively breeding birds, mutualisms, and how to model social evolution.
Keywords: Biology and Life Sciences

Darwin's Gift to Science and Religion - Francisco J. Ayala (The National Academies Press, 2007)
With the publication in 1859 of On the Origin of Species by Means of Natural Selection, Charles Darwin established evolution by common descent as the dominant scientific explanation for nature's diversity. This was to be his gift to science and society; at last, we had an explanation for how life came to be on Earth. Scientists agree that the evolutionary origin of animals and plants is a scientific conclusion beyond reasonable doubt. They place it beside such established concepts as the roundness of the earth, its revolution around the sun, and the molecular composition of matter. That evolution has occurred, in other words, is a fact. Yet as we approach the bicentennial celebration of Darwin's birth, the world finds itself divided over the truth of evolutionary theory. Consistently endorsed as "good science" by experts and overwhelmingly accepted as fact by the scientific community, it is not always accepted by the public, and our schools continue to be battlegrounds for this conflict. From the Tennessee trial of a biology teacher who dared to teach Darwin's theory to his students in 1925 to Tammy Kitzmiller's 2005 battle to keep intelligent design out of the Dover district schools in Pennsylvania, it's clear that we need to cut through the propaganda to quell the cacophony of raging debate. With the publication of Darwin's Gift, a voice at once fresh and familiar brings a rational, measured perspective to the science of evolution. An acclaimed evolutionary biologist with a background in theology, Francisco Ayala offers clear explanations of the science, reviews the history that led us to ratify Darwin's theories, and ultimately provides a clear path for a confused and conflicted public.
Keywords: Biology and Life Sciences; Explore Science

In the Light of Evolution: Volume IV: The Human Condition - National Academy of Sciences (The National Academies Press, 2010)
The Human Condition is a collection of papers by leading evolutionary biologists and philosophers of science that reflect on the Darwinian Revolution as it relates to the human condition at levels ranging from the molecular to the theological. The book focuses on understanding the evolutionary origin of humans and their biological and cultural traits. The Human Condition is organized into three parts: Human Phylogenetic History and the Paleontological Record; Structure and Function of the Human Genome; and Cultural Evolution and the Uniqueness of Being Human. This fourth volume from the In the Light of Evolution (ILE) series, based on a series of Arthur M. Sackler colloquia, was designed to promote the evolutionary sciences. Each volume explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. Individually and collectively, the ILE series interprets phenomena in various areas of biology through the lens of evolution, addresses some of the most intellectually engaging as well as pragmatically important societal issues of our times, and fosters a greater appreciation of evolutionary biology as a consolidating foundation for the life sciences.
Keywords: Biology and Life Sciences

In the Light of Evolution: Volume VI: Brain and Behavior - National Academy of Sciences (The National Academies Press, 2013)
The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia—in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences—and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium "Brain and Behavior," which was sponsored by the National Academy of Sciences on January 20-21, 2012, at the Academy's Arnold and Mabel Beckman Center in Irvine, CA. It is the sixth in a series of Colloquia under the general title "In the Light of Evolution." Specifically, In Light of Evolution: Brain and Behavior focuses on the field of evolutionary neuroscience that now includes a vast array of different approaches, data types, and species. This volume is also available for purchase with the In the Light of Evolution six-volume set.
Keywords: Biology and Life Sciences

Teaching About Evolution and the Nature of Science - National Academy of Sciences (The National Academies Press, 1998)
Today many school students are shielded from one of the most important concepts in modern science: evolution. In engaging and conversational style, Teaching About Evolution and the Nature of Science provides a well-structured framework for understanding and teaching evolution. Written for teachers, parents, and community officials as well as scientists and educators, this book describes how evolution reveals both the great diversity and similarity among the Earth's organisms; it explores how scientists approach the question of evolution; and it illustrates the nature of science as a way of knowing about the natural world. In addition, the book provides answers to frequently asked questions to help readers understand many of the issues and misconceptions about evolution. The book includes sample activities for teaching about evolution and the nature of science. For example, the book includes activities that investigate fossil footprints and population growth that teachers of science can use to introduce principles of evolution. Background information, materials, and step-by-step presentations are provided for each activity. In addition, this volume: Presents the evidence for evolution, including how evolution can be observed today. Explains the nature of science through a variety of examples. Describes how science differs from other human endeavors and why evolution is one of the best avenues for helping students understand this distinction. Answers frequently asked questions about evolution. Teaching About Evolution and the Nature of Science builds on the 1996 National Science Education Standards released by the National Research Council—and offers detailed guidance on how to evaluate and choose instructional materials that support the standards. Comprehensive and practical, this book brings one of today's educational challenges into focus in a balanced and reasoned discussion. It will be of special interest to teachers of science, school administrators, and interested members of the community.
Keywords: Education; Biology and Life Sciences